In the shadow of dissidence: exploring the experiences of descendants of Czechoslovakian dissidents - Doubková, Nikola; Heissler, Radek; Sanders, Edel; Preiss, Marek (Frontiers in Psychology, 2024)
The Communist Party's reign in Czechoslovakia (1948Czechoslovakia ( -1989) ) saw the persecution of thousands of individuals. The State Security campaign "Asanace" (meaning "sanitation") was conducted to expel critics of the regime from the country using psychological and physical terror. Although stories of dissidents are frequently presented in public spaces, little is known about the experiences of their children.To address this gap, we conducted interpretative phenomenological analyses of semistructured in-depth interviews with five adult descendants of Czechoslovakian dissidents.Results: Our analyses revealed that while participants appreciated and were inspired by their parents' dissident activities, they tend to distance themselves from it in order not to live in their parents' shadow. Furthermore, for them, the "Asanace" campaign primarily meant emigration, which in turn affected their sense of self and (national) identity dispersion. Consequently, they experienced feelings of being uprooted and different. Furthermore, they faced challenges acculturating. However, they also recognized their resilience as being rooted in their migration experience and the legacy of their parents' dissidence.Discussion: By highlighting intergenerational differences and the impact of family legacy on individuals' strengths and weaknesses, this study contributes to our understanding of the psychological consequences of living in, escaping from and adjusting to life beyond oppressive regimes.